Looking on the heart ; v.1 expositions of the book of 1 Samuel - Davis, Dale Ralph (Grand Rapids, MI Baker, 1994)
Contents : v.1 : 1 Samuel 1-14. Includes bibliographical references.
Keywords: Bible. O.T. Samuel, 1st, I-XIV -- commentaries